Lignin depolymerization product modified melamine functional additive and preparation method thereof
Through hydrothermal depolymerization reaction and polycondensation treatment of lignin and melamine, a modified melamine-based functional additive with excellent dispersion properties was prepared, which solved the lack of functional properties of melamine-based dispersants in the prior art and The high cost problem has achieved the improvement of application in multiple fields and environmental protection value.
Patent Information
- Application Number
- CN202411318725.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing melamine-based dispersants have problems such as single functional, excessive viscosity, sensitive to raw material mud content, difficult control of dosage, and rising production costs, which limit their wider application, and the between lignin and melamine. The spatial steric resistance problem leads to incomplete modification, complex process, and unstable product performance.
By hydrothermal depolymerization reaction with lignin and melamine, aldehyde compounds, etc., and polycondensation reaction is carried out using acid and alkaline regulators, a modified melamine system with rich phenolic hydroxyl groups and sulfonic acid groups is prepared. Functional additives overcome the steric hindrance problem and achieve simple operating steps and mild reaction conditions.
The prepared additives have strong dispersion properties, compatibility and high water reduction rate. They are suitable for ceramic additives, soil improvers, dye dispersants, concrete water reduction agents, etc., which broadens the application range of lignin and reduces production. Cost promotes sustainable development.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lignin processing, and more specifically relates to a lignin depolymerization product modified melamine-based functional additive and a preparation method thereof. Background Art
[0002] Sulfonated melamine resin, as an anionic surfactant, its official name is sulfonated melamine formaldehyde resin, which is carefully constructed through complex chemical reactions. This process begins with the exquisite combination of melamine and aldehyde compounds to form a hydroxymethyl melamine intermediate, which is then converted into melamine sulfonate under the catalysis of a sulfonating agent, and undergoes a polycondensation reaction to finally condense into a polymer form. The dense sulfonic acid groups in the molecular structure of sulfonated melamine resin, like a pair of invisible hands, show excellent dispersibility for solid particles in the solution, and therefore play an indispensable role in many industrial fields such as ceramic additives, water-coal slurry stabilization, dye dispersion and concrete modification.
[0003] In particular, the sulfonic acid groups in sulfonated melamine resins can intelligently identify and tightly adhere to the surfaces of various powder particles with their strong anchoring properties, and adjust the anchoring strategy according to the polarity differences of the particles. Once adsorption is completed, the extended long chain structure builds a solid space barrier around the particles, effectively preventing aggregation between particles. At the same time, the ionization of the sulfonic acid groups further optimizes the charge distribution on the particle surface and enhances the electrostatic repulsion between particles, thereby ensuring the long-term stability of the dispersed system.
[0004] However, despite the excellent performance of sulfonated melamine resin, it still faces many challenges in practical application. Traditional melamine-based dispersants have problems such as single functionality, high viscosity affecting construction, sensitivity to the mud content of raw materials, difficulty in controlling the dosage, and rising production costs, which limit their wider application. Therefore, the development of a new melamine-based dispersant with low cost and stable performance has become a problem that the industry urgently needs to solve.
[0005] To address these challenges, researchers have turned their attention to lignin, a natural high-molecular organic compound. As the main component of plant skeletons, lignin is not only abundant, inexpensive, environmentally friendly and renewable, but also has the unique ability to provide aromatic compounds, showing great economic and environmental potential. Combining lignin with melamine polymers through chemical modification aims to create a dispersant product with better performance and more comprehensive functions.
[0006] Although there have been studies that have attempted to modify lignin through different pathways to prepare composite dispersants based on lignin and melamine, these methods often have shortcomings such as harsh reaction conditions, complex processes, many by-products, and unstable product performance. Therefore, exploring a new method that is more efficient, environmentally friendly, and can overcome the steric hindrance problem between lignin and melamine has become the focus of current research. This innovation is not only expected to significantly improve the performance of dispersants and broaden their scope of application, but will also inject new vitality into the sustainable development of related industries. Summary of the invention
[0007] In view of the above technical problems, the present invention provides a lignin depolymerization product modified melamine-based functional additive and a preparation method thereof, in order to prepare a lignin depolymerization product modified melamine-based functional additive with small steric hindrance, multiple functions and more thorough modification through simple operating steps, mild reaction conditions, conventional production equipment, low production cost and clean production process, thereby expanding a new technical path for the resource utilization of lignin.
[0008] To achieve the above object, in a first aspect, the present invention provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, comprising the following steps:
[0009] S1, mixing lignin, an activator and water evenly, adding a catalyst for hydrothermal reaction, cooling the reaction liquid, removing the solid residue to obtain a liquid lignin depolymerization product;
[0010] S2, adding melamine, aldehyde compound and water to the lignin depolymerization product, stirring evenly, heating to a first temperature for reaction for a first time period, and then adding a sulfonating agent and heating to a second temperature for reaction for a second time period;
[0011] S3, cooling to a third temperature, adding an acidic regulator to adjust the reaction system to a first pH value, conducting an acidic polycondensation reaction for a third time period, adding an alkaline regulator to adjust the reaction system to a second pH value, heating to a fourth temperature to react for a fourth time period, cooling, discharging, and spray drying to obtain the lignin depolymerization product modified melamine functional additive.
[0012] The lignin used in the present invention is selected from one or more of masson pine, reed, giant fungus grass, wheat straw, birch, bagasse, ash, king bamboo grass, eucalyptus, reed, poplar, Achnatherum splendens and rice straw.
[0013] The acidic regulator used in the present invention is one or more of sulfamic acid, oxalic acid, tartaric acid, sulfuric acid, phosphoric acid, citric acid, salicylic acid, maleic acid, succinic acid and benzoic acid.
[0014] The alkaline regulator used in the present invention is one or more of sodium hydroxide, sodium pyrophosphate, potassium hydroxide, sodium dipolyphosphate, sodium tripolyphosphate, sodium polyphosphate and sodium tetraborate.
[0015] The present invention utilizes an activator and a catalyst to perform a hydrothermal depolymerization reaction on lignin, and the number of main active functional groups such as phenolic hydroxyl groups of the depolymerized lignin is significantly increased, which is conducive to further modification and improves its application value in various fields. The lignin depolymerization product is used as a raw material and directly reacted with melamine and aldehyde compounds under specific conditions to prepare a lignin depolymerization product modified melamine-based dispersant, the preparation process is simple, the reaction conditions are mild, the obtained product has abundant phenolic hydroxyl groups and sulfonic acid groups, has strong reaction activity, and can produce effective electrostatic repulsion and steric hindrance on pulp particles.
[0016] According to some preferred embodiments, the amount of each raw material is as follows by mass percentage:
[0017] Lignin 5.0%~20.0%;
[0018] Activator 5%~10%;
[0019] Catalyst 0.3%~1.0%;
[0020] Melamine 6.5% to 15.5%;
[0021] Aldehyde compounds 19.0%~34.0%;
[0022] Sulfonating agent 10.0%~18.0%;
[0023] Acidity regulator 0.1%~1.5%;
[0024] Alkaline regulator 0.2%~0.8%;
[0025] Water 25.0%~50.0%.
[0026] According to some preferred embodiments, the activator is an alkaline activator, preferably, the alkaline activator is one or more of KOH, NaOH, Ca(OH)2, Mg(OH)2, LiOH, and MgO.
[0027] According to some preferred embodiments, the catalyst is a metal catalyst, preferably, the metal catalyst is one or more of Ni-Fe, Ni-Co, Ni-Mg, Ni-Zn, Ni-Al, and Ni-Zn-Co.
[0028] According to some preferred embodiments, the aldehyde compound is one or more of formaldehyde, acetaldehyde, glyoxal, butyraldehyde, isobutyraldehyde or glutaraldehyde.
[0029] According to some preferred embodiments, the sulfonating agent is one or more of sodium sulfite, sodium bisulfite, sodium pyrosulfite, potassium sulfite, ammonium sulfite, aminosulfonic acid, and sodium p-aminobenzenesulfonate.
[0030] According to some preferred embodiments, the first temperature is 50-80° C., and the first time period is 0.5-2.5 hours; preferably, the second temperature is 75-105° C., and the second time period is 1-3 hours.
[0031] According to some preferred embodiments, the third temperature is 55-85°C, the first pH value is 4-6, and the third time period is 0.5-2.5h; preferably, the fourth temperature is 60-90°C, the second pH value is 8-10, and the fourth time period is 2-4h.
[0032] According to some preferred embodiments, in S1, the temperature of the hydrothermal reaction is 180-250°C, the reaction time is 1-5h, and the reaction liquid is cooled to 35-50°C.
[0033] In the second aspect, the inventors provide a lignin depolymerization product modified melamine-based functional additive, which is prepared by the preparation method of the first aspect of the present invention. Preferably, the relative molecular mass Mn of the lignin depolymerization product modified melamine-based functional additive is 4300-40000.
[0034] Different from the prior art, the above technical scheme obtains lignin depolymerization products with rich active functional groups such as phenolic hydroxyl, methoxy, and ester groups by depolymerizing lignin, so it is easier to carry out chemical modification. The lignin depolymerization product modified melamine-based functional additives are obtained by hydroxymethylation, sulfonation, acid polymerization, alkaline reforming and spray drying, which have strong dispersibility, good compatibility and high water reduction rate. The lignin depolymerization product modified melamine-based functional additives of the present invention have multiple functions such as water reduction, grinding aid, dispersion and enhancement, and can be used as ceramic additives, soil conditioners, dye dispersants, concrete water reducers and water-coal slurry dispersants, etc., showing strong market potential and environmental value. The present invention uses lignin, a by-product of the pulping industry, as raw material, which is not only rich in resources and low in cost, but also has a simple preparation process and mild reaction conditions. It also promotes the utilization of waste resources and helps achieve the carbon peak and carbon neutrality goals.
[0035] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the written contents of the specification, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the specific implementation methods of the present application are explained below. DETAILED DESCRIPTION
[0036] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description in conjunction with the specific embodiments listed. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0037] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0038] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0039] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.
[0040] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.
[0041] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.
[0042] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.
[0043] Unless otherwise expressly specified or limited, in the description of the embodiments of the present application, the terms such as "install", "connect", "connect", "fix", "set", etc. used should be understood in a broad sense. For example, the "connection" can be a fixed connection, a detachable connection, or an integrated setting; it can be a mechanical connection, an electrical connection, or a communication connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For technicians in the technical field to which the present application belongs, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0044] The existing melamine-based dispersant technology has multiple defects: functional products are scarce and difficult to meet the diverse needs of the market; the high viscosity characteristics limit the application in high-blending, low water-binder ratio materials, and it is sensitive to the mud content of sand and gravel aggregates and has poor construction adaptability; the rising price of raw material melamine has pushed up production costs and further exacerbated the application challenges. In addition, the existing research methods for lignin-modified melamine polymers are complex, the reaction conditions are harsh, the product performance is single, and there are problems such as incomplete modification and difficulty in synthesis, which limit its wide application.
[0045] In view of this, the present invention aims to develop a low-cost, stable-performance lignin depolymerization product modified melamine-based functional additive, which innovatively uses alkali activators and metal catalysts to efficiently depolymerize lignin, and accurately regulates the directional polymerization process of the depolymerization product, successfully overcoming the steric hindrance problem between lignin and melamine polymers, and achieving effective reaction and functional improvement. The dispersant of the present invention not only has a low dosage and excellent dispersion performance, but also has a wide range of applications, covering ceramic additives, soil conditioners, dye dispersants, concrete water reducers, and water-coal slurry dispersants and other fields, effectively broadening the utilization of lignin, promoting the development of renewable resources and the development of the circular economy, and providing strong technical support for the realization of environmental protection and energy conservation, low-carbon economy, and carbon peak and carbon neutrality goals.
[0046] In the present invention, unless otherwise specified, the reagents used are conventional commercial products in the art.
[0047] In the present invention, unless otherwise specified, the test methods and equipment are the test methods and equipment conventionally used in the art.
[0048] Example 1
[0049] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0050] In a reactor, 87.8 kg of Phyllostachys lignin, 58.9 kg of potassium hydroxide, and 155.1 kg of water were stirred evenly, and 6.1 kg of Ni-Fe was added to react at 250 ° C for 3.4 hours. After cooling to 48 ° C, the solid residue was removed to obtain the lignin depolymerization product. 164.9 kg of water, 100.4 kg of melamine, and 294.6 kg of formaldehyde were added to the depolymerization product, stirred evenly, and then heated to 75 ° C and reacted for 2.0 hours. 122.2 kg of sodium sulfite was added, and the temperature was raised to 100 ° C and continued to react for 2.0 hours. After lowering the system temperature to 60 ° C, 6.8 kg of salicylic acid was added, and the pH value of the system was adjusted to about 5, and the reaction was carried out for 2 hours. Then 3.2 kg of sodium hydroxide was added to adjust the pH value of the system to about 10, and the reaction was carried out at a reaction temperature of 100 ° C for 2.0 hours. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230° C. and the outlet temperature was 80° C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 14850.
[0051] Example 2
[0052] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0053] In a reactor, 148.3kg of reed lignin, 51.7kg of potassium hydroxide, and 162.1kg of water were stirred evenly, and 7.2kg of Ni-Co was added to react at 250°C for 3.4h. After cooling to 48°C and removing the solid residue, the lignin depolymerization product was obtained. 177.9kg of water, 81.1kg of melamine, and 228.4kg of acetaldehyde were added to the depolymerization product, stirred evenly, and then heated to 60°C and reacted for 2.5h. 132.8kg of sodium pyrosulfite was added, and the temperature was raised to 70°C and the reaction continued for 3.5h. After lowering the system temperature to 65°C, 6.5kg of benzoic acid was added, and the pH value of the system was adjusted to about 5, and the reaction was carried out for 2.5h. Then 4.0kg of potassium hydroxide was added to adjust the pH value of the system to about 9, and the reaction was carried out at a reaction temperature of 70°C for 3.5h. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230° C. and the outlet temperature was 80° C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 25650.
[0054] Example 3
[0055] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0056] In a reactor, 55.3kg of Achnatherum splendens lignin, 55.8kg of potassium hydroxide, and 150.2kg of water were stirred evenly, and 4.2kg of Ni-Zn was added to react at 250°C for 3.4h. After cooling to 48°C, the solid residue was removed to obtain the lignin depolymerization product. 154.8kg of water, 119.2kg of melamine, and 310.9kg of formaldehyde were added to the depolymerization product and stirred evenly, and the temperature was raised to 95°C and reacted for 1.5h. 139.1kg of sodium bisulfite was added, and the temperature was raised to 100°C and the reaction was continued for 3.0h. After lowering the system temperature to 55°C, 5.7kg of aminosulfonic acid was added to adjust the pH value of the system to about 6, and the reaction was carried out for 2.0h. Then 4.8kg of sodium dipolyphosphate was added to adjust the pH value of the system to about 8, and the reaction was carried out at a reaction temperature of 100°C for 2.5h. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230° C. and the outlet temperature was 80° C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 15760.
[0057] Example 4
[0058] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0059] In a reactor, 114.6 kg of poplar lignin, 60.4 kg of potassium hydroxide, and 160.5 kg of water were stirred evenly, and 7.8 kg of Ni-Fe was added to react at 250 ° C for 3.4 hours. After cooling to 48 ° C, the solid residue was removed to obtain the lignin depolymerization product. 174.5 kg of water, 87.2 kg of melamine, and 235.9 kg of formaldehyde were added to the depolymerization product and stirred evenly, and the temperature was raised to 80 ° C and reacted for 2.0 hours. 152.4 kg of potassium sulfite was added, and the temperature was raised to 95 ° C and the reaction was continued for 4.0 hours. After the system temperature was lowered to 50 ° C, 2.9 kg of tartaric acid was added, and the pH value of the system was adjusted to about 6, and the reaction was carried out for 2.0 hours. Then 3.8 kg of sodium pyrophosphate was added to adjust the pH value of the system to about 10, and the reaction was carried out at a reaction temperature of 95 ° C for 3.0 hours. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 19280.
[0060] Example 5
[0061] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0062] In the reactor, 100.3kg of ash lignin, 64.7kg of potassium hydroxide, and 259.6kg of water were stirred evenly, and 3.6kg of Ni-Al was added to react at 250°C for 3.4h. After cooling to 48°C, the solid residue was removed to obtain the lignin depolymerization product. 192.4kg of water, 70.1kg of melamine, and 190.6kg of glyoxal were added to the depolymerization product and stirred evenly, heated to 85, and reacted for 2.5h. 109.4kg of sodium bisulfite / ammonium sulfite (mass ratio of 2:1) was added, and the temperature was raised to 95°C and the reaction continued for 2.5h. After the system temperature was lowered to 50°C, 1.9kg of sulfuric acid was added to adjust the pH value of the system to about 3, and the reaction was carried out for 2.0h. Then 7.4kg of sodium phosphate was added to adjust the pH value of the system to about 10, and the reaction was carried out at a reaction temperature of 95°C for 2.0h. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230° C. and the outlet temperature was 80° C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 17720.
[0063] Example 6
[0064] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0065] In a reactor, 70.3kg of royal bamboo lignin and birch lignin (lignin obtained with a mass ratio of royal bamboo and birch of 3:1), 75.1kg of potassium hydroxide, and 189.6kg of water were stirred evenly, and 5kg of Ni-Fe was added to react at 250°C for 3.4h. After cooling to 48°C, the solid residue was removed to obtain the lignin depolymerization product. 155.4kg of water, 129.7kg of melamine, and 229.9kg of butyraldehyde were added to the depolymerization product and stirred evenly, and the temperature was raised to 70 and reacted for 1.5h. 129.2kg of sodium sulfite / sodium aminobenzenesulfonate (mass ratio of 2:1) was added, and the temperature was raised to 90°C and the reaction was continued for 3.5h. After the system temperature was lowered to 50°C, 11.5kg of succinic acid was added, and the pH value of the system was adjusted to about 4, and the reaction was continued for 3.0h. Then, 4.3 kg of sodium hydroxide / potassium hydroxide (mass ratio of 1:1) was added to adjust the pH value of the system to about 8, and the reaction was carried out at a reaction temperature of 90°C for 2.5 hours. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer. The inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product was a lignin depolymerization product modified melamine functional additive. The molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 32720.
[0066] Example 7
[0067] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0068] In a reactor, 144.6 kg of Masson pine and bagasse lignin (lignin obtained with a mass ratio of Masson pine and bagasse of 4:1), 53.1 kg of potassium hydroxide, and 214.7 kg of water were stirred evenly, and 9.4 kg of Ni-Mg was added to react at 250 ° C for 3.4 hours. After cooling to 48 ° C, the solid residue was removed to obtain the lignin depolymerization product. 144.3 kg of water, 90.3 kg of melamine, and 232.9 kg of glutaraldehyde were added to the depolymerization product, stirred evenly, heated to 65 ° C, and reacted for 2.5 hours. 100.2 kg of sodium pyrosulfite / sodium para-aminobenzenesulfonate (mass ratio of 2:1) was added, and the temperature was raised to 80 ° C and the reaction was continued for 3.5 hours. After the system temperature was lowered to 60 ° C, 6.2 kg of phosphoric acid was added to adjust the pH value of the system to about 5.5, and the reaction was continued for 3.0 hours. Then, 4.3 kg of sodium tetraborate was added to adjust the pH value of the system to about 9, and the reaction was carried out at a reaction temperature of 80°C for 3.0 hours. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer. The inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product was a lignin depolymerization product modified melamine functional additive. The molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 28270.
[0069] Example 8
[0070] This example provides a method for preparing a melamine-based functional additive modified by a lignin depolymerization product, the method comprising the following steps:
[0071] In a reactor, 98.6 kg of eucalyptus and poplar lignin (lignin obtained with a mass ratio of eucalyptus and poplar of 2:1), 64.5 kg of potassium hydroxide, and 157.9 kg of water were stirred evenly, and 6.4 kg of Ni-Zn was added to react at 250 ° C for 3.4 hours. After cooling to 48 ° C, the solid residue was removed to obtain the lignin depolymerization product. 132.1 kg of water, 135.5 kg of melamine, and 280.2 kg of formaldehyde were added to the depolymerization product and stirred evenly, heated to 75 ° C, and reacted for 2.5 hours. 114.8 kg of sodium pyrosulfite was added, and the temperature was raised to 100 ° C and the reaction was continued for 2.5 hours. After the system temperature was lowered to 65 ° C, 7.8 kg of salicylic acid / maleic acid (mass ratio: 3:1) was added, and the pH value of the system was adjusted to about 6, and the reaction was 1.5 hours. Then 2.2 kg of sodium hydroxide was added to adjust the pH value of the system to about 9, and the reaction was carried out at a reaction temperature of 100 ° C for 1.5 hours. After cooling, the material was discharged to obtain a brown liquid product, and the obtained liquid was dried by a spray dryer, and the inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product was a lignin depolymerization product modified melamine functional additive, and its molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 27230.
[0072] The performance of the melamine-based functional additive modified by the lignin depolymerization product obtained in Examples 1-8 above was tested. The test method is as follows:
[0073] The specific steps of using gel permeation chromatography to test its molecular weight are:
[0074] The sample of the additive was freeze-dried in a vacuum freeze dryer for 3 days before molecular structure characterization test. The number average molecular weight (M) of the product was determined using a Waters 1515 gel permeation chromatograph (GPC) and a Waters 2414 refractive index detector. n ), weight average molecular weight (M w ) and polydispersity index (PDI). Before calibration, a series of standard substances were prepared into a 0.3% aqueous solution, and the standard working curve was determined; a sample solution with a concentration of about 0.3% was prepared with 0.1 mol / L sodium nitrate, and then the molecular weight distribution was determined.
[0075] Comparative Example 1
[0076] This comparative example provides a method for preparing a dispersant, which comprises the following steps:
[0077] In the reactor, 154.8kg water, 119.2kg melamine and 310.9kg formaldehyde were stirred evenly, heated to 95°C and reacted for 1.5h. 139.1kg sodium bisulfite was added, and the temperature was raised to 100°C and the reaction was continued for 3.0h. After the temperature of the system solution was lowered to 55°C, 5.7kg aminosulfonic acid was added to adjust the pH value of the system to about 6 and reacted for 2.0h. Then 4.8kg sodium dipolyphosphate was added to adjust the pH value of the system to about 8, and the reaction was carried out at a reaction temperature of 100°C for 2.5h. After cooling, the material was discharged to obtain a brown liquid product. The obtained liquid was dried with a spray dryer. The inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product is a melamine-based functional additive. The molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 11450.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a dispersant, which comprises the following steps:
[0080] 55.3kg of Achnatherum splendens lignin, 154.8kg of water, 119.2kg of melamine and 310.9kg of formaldehyde were stirred evenly, heated to 95°C and reacted for 1.5h. 139.1kg of sodium bisulfite was added, and the temperature was raised to 100°C and the reaction was continued for 3.0h. After the temperature of the system solution was lowered to 55°C, 5.7kg of aminosulfonic acid was added to adjust the pH value of the system to about 6 and reacted for 2.0h. Then 4.8kg of sodium dipolyphosphate was added to adjust the pH value of the system to about 8, and the reaction was carried out at a reaction temperature of 100°C for 2.5h. After cooling, the material was discharged to obtain a brown liquid product. The obtained liquid was dried with a spray dryer. The inlet temperature of the spray tower was 230°C and the outlet temperature was 80°C. The obtained solid product is a functional additive of melamine modified by lignin depolymerization product. The molecular weight was tested by gel permeation chromatography, and the relative molecular mass Mn was measured to be 13650.
[0081] The performance of the functional additive prepared above was tested.
[0082] Application Example 1
[0083] Application of melamine functional additives modified by lignin depolymerization products in ceramic additives
[0084] The composition (wt%) of the ceramic slurry used in this application example is shown in Table 1. The products obtained in Examples 1-8 and Comparative Examples 1-2 are added to the ceramic slurry as ceramic additives, and the fluidity, viscosity and green body flexural strength of the obtained mixtures are compared. The results are shown in Table 2, wherein the fluidity test is determined according to the national standard GB / T1723-93; the viscosity test is determined according to the national standard GB / T 2794-2013; and the green body flexural strength test refers to the international GB / T 3810.4-2006 Part 4: Determination of rupture modulus and breaking strength.
[0085] Table 1 Ceramic slurry composition (wt%)
[0086]
[0087] Table 2 Fluidity, viscosity and green body flexural strength of products after adding ceramic additives
[0088]
[0089] Note: Different from Example 3, Comparative Example 1 is a melamine-based functional additive product prepared directly from melamine, formaldehyde and sodium bisulfite without adding lignin, and Comparative Example 2 is a melamine-based functional additive product modified by a lignin depolymerization product prepared from melamine, formaldehyde and sodium bisulfite under the condition of adding the same lignin as in Example 3.
[0090] It can be seen from the results of the above table that when the molecular weight of the product is too large, it will affect the flow properties; when the molecular weight is too small, it will affect the green body flexural strength. Compared with other products, under the same dosage, the molecular weight of the products obtained in Example 3 (the molecular weight of the obtained additive is 15760) and Example 5 (the molecular weight of the obtained additive is 17720) is appropriate, not only the outflow time of the ceramic slurry is fast, but also the green body flexural strength is high, which is suitable as a ceramic additive. However, the ceramic slurry with the additives added in Comparative Examples 1 and 2 has a long outflow time and low green body flexural strength, and high viscosity, which reduces the construction efficiency of processes such as grouting, impregnation or coating, and increases the difficulty of process control of ceramic products with rapid prototyping or high-precision requirements, which has a negative impact on the overall performance of ceramic products, increases scrap rate and cost, and reduces molding accuracy and surface quality. Therefore, compared with the additives provided in Comparative Examples 1-2, the lignin depolymerization product modified melamine-based functional additives provided by the present invention are more suitable as ceramic dispersants, especially when the molecular weight of the lignin depolymerization product modified melamine-based functional additives is between 5000 and 20000, it has the excellent effects of short ceramic slurry outflow time and high green body flexural strength as a ceramic additive.
[0091] Application Example 2
[0092] Application of melamine functional additives modified by lignin depolymerization products as dye dispersants
[0093] In order to investigate the possibility of the product as a dye dispersant, the products obtained in Examples 1-8 and Comparative Examples 1-2 were added to Olive T dye in equal amounts, with the added amount being 150% of the dye. The heat stability of various additives to vat dyes was tested and rated according to HG / T 3507-2008 "Sodium lignin sulfonate dispersants" and HG / T 3399 2001 "Determination of dye diffusion properties", and the test results are shown in Table 3.
[0094] Table 3 Comparison of heat resistance stability of products
[0095]
[0096] From the results in Table 3, it can be seen that when the molecular weight of the obtained product is too large, it will affect its dispersibility and cause the dye to re-agglomerate; when the molecular weight is too small, it will affect its high temperature stability. Compared with other products, the products obtained in Example 2 (the molecular weight of the obtained auxiliary agent is 25650) and Example 8 (the molecular weight of the obtained auxiliary agent is 27230) have appropriate molecular weights and better heat resistance stability, and are suitable for use as dye dispersants. Therefore, based on the above, the lignin depolymerization product modified melamine functional auxiliary agent obtained by the present invention is suitable for use as a dye dispersant when the molecular weight is between 15000 and 30000.
[0097] Application Example 3
[0098] Application of melamine-based functional additives modified by lignin depolymerization products as concrete water reducers
[0099] In order to investigate the possibility of the product as a concrete admixture, the performance of the products obtained in Examples 1-8 and Comparative Examples 1-2 was tested. The method was carried out with reference to JG / T223-2007, with Evergreen cement as the research object. The test results are shown in Table 4.
[0100] Table 4 Comparison of product strength and fluidity
[0101]
[0102] From the results in Table 4, it can be seen that when the molecular weight of the obtained product is too large, it will affect its flow properties; when the molecular weight is too small, it will affect its compressive strength. Compared with other products, the products obtained in Example 4 (the molecular weight of the obtained additive is 19280) and Example 5 (the molecular weight of the obtained additive is 17720) have appropriate molecular weights, large net slurry fluidity, large compressive strength and small change value after placement, which are suitable for concrete water reducers. Therefore, based on the above, the lignin depolymerization product modified melamine functional additive obtained by the present invention is suitable for concrete water reducers when the molecular weight is between 10000 and 25000.
[0103] Application Example 4
[0104] Application of melamine functional additive modified by lignin depolymerization product as dispersant in coal water slurry
[0105] In order to investigate the possibility of the product as a water-coal slurry additive, the dispersibility and stability of the water-coal slurry were tested on the products obtained in Examples 1-8 and Comparative Examples 1-2. Black Mountain coal was selected as the research object. After crushing, grinding, screening and grading, a certain amount of water and the product as a dispersant (the addition amount was 0.3wt%) were added, and stirred evenly to obtain water-coal slurries of different concentrations. The test results are shown in Table 5.
[0106] Table 5 Comparison of dispersibility and stability of products
[0107]
[0108] From the results in Table 5, it can be seen that when the molecular weight of the obtained product is too large, the additive may cause a significant increase in the viscosity of the water-coal slurry, thereby reducing the fluidity of the water-coal slurry; when the molecular weight is too small, the additive may perform poorly in maintaining the suspended state of coal particles, and cannot provide sufficient protection against sedimentation and aggregation, which will reduce the stability of the water-coal slurry. Compared with other products, the products obtained in Example 7 (the molecular weight of the obtained additive is 28270) and Example 8 (the molecular weight of the obtained additive is 27230) have appropriate molecular weights, high slurry concentrations, and high viscosity, and are suitable as water-coal slurry dispersants. Therefore, based on the above, when the molecular weight of the lignin depolymerization product modified melamine-based functional additive obtained by the present invention is between 20,000 and 35,000, it is suitable as a water-coal slurry dispersant.
[0109] Application Example 5
[0110] Application of melamine-based functional additives modified by lignin depolymerization products as soil conditioners
[0111] In order to investigate the possibility of the product as a soil conditioner, the performance of the products obtained in Examples 1-8 and Comparative Examples 1-2 was tested. The method was carried out with reference to GB / T 42817-2023, and yellow-red soil was used as the soil matrix for the study. The test results are shown in Table 6.
[0112] Table 6 Comparison of soil bulk density, soil pH value and soil organic matter of the products
[0113]
[0114] From the results in Table 6, it can be seen that the additive with a smaller molecular weight has a smaller effect on the soil bulk density and organic matter content, while the additive with a larger molecular weight has a greater effect on the soil bulk density and organic matter content. The additive with a large molecular weight can increase the contact area and structural stability between the soils, thereby reducing the bulk density. Compared with other products, the products obtained in Example 7 (the molecular weight of the obtained additive is 28270) and Example 8 (the molecular weight of the obtained additive is 27230) have appropriate molecular weights, the best soil bulk density improvement effect, the largest increase in soil pH, and the most obvious improvement effect on soil organic matter content, and are suitable as soil conditioners. Therefore, based on the above, when the molecular weight of the lignin depolymerization product modified melamine functional additive obtained by the present invention is between 25,000 and 40,000, it is suitable as a soil conditioner.
[0115] In summary, the present invention obtains a lignin depolymerization product having abundant active functional groups such as phenolic hydroxyl, methoxyl, and ester groups by depolymerizing lignin, and obtains a lignin depolymerization product modified with melamine functional additives through hydroxymethylation, sulfonation, acid polymerization, alkaline reforming, and spray drying, which has good dispersibility and compatibility, and has a high water reduction rate. Therefore, the lignin depolymerization product modified with melamine functional additives of the present invention has multiple functions such as water reduction, grinding aid, dispersion, and enhancement, and can be used as a ceramic additive, soil conditioner, dye dispersant, concrete water reducer, and water-coal slurry dispersant, etc., showing strong market potential and environmental value.
[0116] Finally, it should be noted that although the above embodiments have been described in the text of the specification of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the text of the specification of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.
Claims
1. A method for preparing a melamine-based functional additive modified by a lignin depolymerization product, characterized in that: The following steps are involved: S1, mixing lignin, an activator and water evenly, adding a catalyst for hydrothermal reaction, cooling the reaction liquid, removing the solid residue to obtain a liquid lignin depolymerization product; S2, adding melamine, aldehyde compound and water to the lignin depolymerization product, stirring evenly, heating to a first temperature for reaction for a first time period, and then adding a sulfonating agent and heating to a second temperature for reaction for a second time period; S3, cooling to a third temperature, adding an acidic regulator to adjust the reaction system to a first pH value, conducting an acidic polycondensation reaction for a third time period, adding an alkaline regulator to adjust the reaction system to a second pH value, heating to a fourth temperature to react for a fourth time period, cooling, discharging, and spray drying to obtain the lignin depolymerization product modified melamine functional additive.
2. The preparation method according to claim 1, characterized in that: Calculated by mass percentage, the amount of each raw material is: Lignin 5.0%~20.0%; Activator 5%~10%; Catalyst 0.3%~1.0%; Melamine 6.5% to 15.5%; Aldehyde compounds 19.0%~34.0%; Sulfonating agent 10.0%~18.0%; Acidity regulator 0.1%~1.5%; Alkaline regulator 0.2%~0.8%; Water 25.0%~50.0%.
3. The preparation method according to claim 1, characterized in that: The activator is an alkali activator. Preferably, the alkali activator is one or more of KOH, NaOH, Ca(OH)2, Mg(OH)2, LiOH, and MgO.
4. The preparation method according to claim 1, characterized in that: The catalyst is a metal catalyst. Preferably, the metal catalyst is one or more of Ni-Fe, Ni-Co, Ni-Mg, Ni-Zn, Ni-Al, and Ni-Zn-Co.
5. The preparation method according to claim 1, characterized in that: The aldehyde compound is one or more of formaldehyde, acetaldehyde, glyoxal, butyraldehyde, isobutyraldehyde or glutaraldehyde.
6. The preparation method according to claim 1, characterized in that: The sulfonating agent is one or more of sodium sulfite, sodium bisulfite, sodium pyrosulfite, potassium sulfite, ammonium sulfite, aminosulfonic acid, and sodium p-aminobenzenesulfonate.
7. The preparation method according to claim 1, characterized in that: The first temperature is 50-80° C., and the first time period is 0.5-2.5 hours; Preferably, the second temperature is 75-105° C., and the second time period is 1-3 hours.
8. The preparation method according to claim 1, characterized in that: The third temperature is 55-85° C., the first pH value is 4-6, and the third time period is 0.5-2.5 hours; Preferably, the fourth temperature is 60-90° C., the second pH value is 8-10, and the fourth time period is 2-4 hours.
9. The preparation method according to claim 1, characterized in that: In S1, the temperature of the hydrothermal reaction is 180-250°C, the reaction time is 1-5h, and the reaction liquid is cooled to 35-50°C.
10. A melamine-based functional additive modified by a lignin depolymerization product, characterized in that: Prepared by the preparation method of any one of claims 1 to 9, preferably, the relative molecular mass Mn of the lignin depolymerization product modified melamine-based functional additive is 4300-40000.
Citation Information
Patent Citations
Alkali lignin modified melamine series water coal slurry additive and preparation process thereof
CN102031169A
Method for preparing dispersant from lignin degradation product and application of dispersant
CN110078877A
Preparation of high-activity Ni-Co bimetallic catalyst and application of high-activity Ni-Co bimetallic catalyst in catalytic hydrocracking of lignin
CN115970697A
Composition, method for producing same, and dispersant
IN202147004827A
